Salinity stress on various physiological and biochemical attributes of two distinct maize (Zea mays L.) genotypes. (3rd July 2018) - Zahra, Noreen; Mahmood, Saqib; Raza, Zulfiqar Ali
ABSTRACT: Present study investigates the effect of salinity stress on physiological and biochemical characteristics of two maize genotypes cultivated under controlled growth conditions. The selected maize genotypes being salt-tolerant and salt-sensitive were respectively designated as Sahwal-2002 and Sadaf. The experiment was conducted in triplicates, two varieties, three priming treatments and two salinity levels, in the Government College University, Faisalabad. The antioxidants activity was measured by comparing the tolerance in response to acute and prolonged salinity treatment. The difference of genotype with salinity tolerance as well as seed priming with phenylalanine were not dependent on antioxidant activity when salt exposure was prolonged. The results show that an indirect relationship was present for PAL seed priming and oxidative damage due to salt. The antioxidant enzymes present in plant effectively reduced the oxidative damage of salt and thus, increased the overall crop yield.